2014
DOI: 10.1007/s11357-014-9700-x
|View full text |Cite
|
Sign up to set email alerts
|

Are the leukocyte telomere length attrition and telomerase activity alteration potential predictor biomarkers for sporadic TAA in aged individuals?

Abstract: A large variability in occurrence, complications, and age/gender manifestations characterizes individual susceptibility of sporadic thoracic aortic aneurysms (TAA), even in subjects with the same risk factor profiles. The reasons are poorly understood. On the other hand, TAA pathophysiology mechanisms remain unclear than those involved in abdominal aorta aneurysms. However, recent evidence is suggesting a crucial role of biological ageing in inter-individual risk variation of cardiovascular diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
1
23
1
Order By: Relevance
“…Interestingly, we found that their combined genotype was significantly represented in sporadic TAA than controls. In subsequent investigations, we also have shown that cases with this risk genotype showed a higher systemic inflammatory mediator levels [8,126], a significant inflammatory/immune infiltrate [8,126],a typical MD phenotype [127], a lower telomere length [128,129] and positive correlations with histopatological abnormalities [126,127],hypertension, smoking, and aging [8,[126][127][128][129]. Consequently, our findings (even if prevalently of associated type) led us to suggest the key role of TLR-4 pathway in the onset of this disease [4,8].…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 75%
“…Interestingly, we found that their combined genotype was significantly represented in sporadic TAA than controls. In subsequent investigations, we also have shown that cases with this risk genotype showed a higher systemic inflammatory mediator levels [8,126], a significant inflammatory/immune infiltrate [8,126],a typical MD phenotype [127], a lower telomere length [128,129] and positive correlations with histopatological abnormalities [126,127],hypertension, smoking, and aging [8,[126][127][128][129]. Consequently, our findings (even if prevalently of associated type) led us to suggest the key role of TLR-4 pathway in the onset of this disease [4,8].…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 75%
“…Furthermore, we detected that these alleles influence vascular biological aging, evaluating the gold standard aging marker, the telomere length, in a small number of cases and controls, selected randomly, but having the same age and gender. It characterized the 85% of the cases examined, which had lower telomere length, higher levels of mediators, increased amount of chronic inflammatory infiltrate [33,66,67].…”
Section: Tlr-4 Pathwaymentioning
confidence: 99%
“…Accordingly, it has been demonstrated that in peripheral blood mononuclear cells from aged individuals, the exercise training reduces protein expression of TLR-2 and TLR-4 [ 78 ]. Similarly, physical exercise also seems to improve the circulating levels of endothelial progenitor cells (EPCs), cells related to both endothelial turnover, cardiovascular repair and regeneration, and adult angiogenesis [ 18 ]. Thus, physical exercise is associated with a good health of endothelium, an essential component of stroma of all tissues and organs [ 18 ].…”
Section: Physical Activity As Another Beneficial Antiageing/anti-imentioning
confidence: 99%
“…Similarly, physical exercise also seems to improve the circulating levels of endothelial progenitor cells (EPCs), cells related to both endothelial turnover, cardiovascular repair and regeneration, and adult angiogenesis [ 18 ]. Thus, physical exercise is associated with a good health of endothelium, an essential component of stroma of all tissues and organs [ 18 ]. Its dysfunction has been detected to contribute to the onset of the major number of ARDs, CVDs, and neurodegenerative diseases included, as amply described in our recent studies [ 13 , 18 ].…”
Section: Physical Activity As Another Beneficial Antiageing/anti-imentioning
confidence: 99%